1970
DOI: 10.1203/00006450-197003000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Ventilatory Measurements in Subjects 1 Month-5 Years of Age: Normal Results and Observations in Disease

Abstract: ExtractUsing the total body plethysmograph, a method for the measurement of lung volume and airway resistance was developed for infants and young children of 1 month-5 years of age. The subjects were studied in a supine position using a reproducible method of sedation. The procedure providing the most consistent results involved use of a Rendell-Baker mask directly controlled by the operator while the subjects were breathing through the nose. Availability of an oscilloscope permitted immediate detection of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
26
3

Year Published

1981
1981
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(35 citation statements)
references
References 11 publications
6
26
3
Order By: Relevance
“…As in our previous study, the values of pulmonary functions reported in this work showed good agreement with data in other studies (3,5,7,10,11,15). The increased ventilation during carbon dioxide-induced hyperventilation was due mainly to an increased tidal volume.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As in our previous study, the values of pulmonary functions reported in this work showed good agreement with data in other studies (3,5,7,10,11,15). The increased ventilation during carbon dioxide-induced hyperventilation was due mainly to an increased tidal volume.…”
Section: Discussionsupporting
confidence: 82%
“…Strong linear relationships have been shown between resistance or conductance and lung volumes in other studies (5,13). We have tried to measure lung volumes with the body plethysmograph and gas dilution techniques but did not succeed because the unsedated infants were awakened by the experimental manipulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported in awake adult man (2). Such changes could be caused by an increase in airway resistance due to partial airway obstruction (4) or to the flow resistance of the pneumotachograph. The latter explanation is unlikely, as flow resistance through the mask and pneumotachograph was very low-less than 10% of the expected total airway resistance (8)-and comparable to values published for other mask or pneumotachograph techniques (9, 10).…”
Section: Discussionsupporting
confidence: 77%
“…The mean tidal volume was equal during two consecutive measurements as was the respiratory rate. The mean tidal volume of 17.1 mL·kg -1 is higher than the 12.0 and 8.8 mL·kg -1 observed by TAUSSIG et al [7] and by DOERSHUK et al [16], respectively. In the study by DOERSHUK et al [16], the children were sedated, which may reduce the tidal volume [5].…”
Section: Discussionmentioning
confidence: 44%